A RELATIONAL PERSPECTIVE ON TURNOVER: EXAMINING AFFECTIVE, CONTINUANCE, AND NORMATIVE PREDICTORS - Bambang Setiono; Christian Haposan Pangaribuan; Rith Analin Osok; Martinus Fieser Sitinjak (Journal of Management and Business, 2019)
High rate for employee turnover intention may lead to significant expenses of an organization, including the direct costs of replacing an employee and the indirect costs related to loss of experience and lowered productivity. The aim of the study is to investigate the influence of organizational commitment toward the employee turnover. The research method used in the study is quantitative approach. The primary data were collected by distributing questionnaires to 100 employees of a state-owned electricity corporation in Jakarta, Indonesia. Multiple linear regression shows that all three components of organizational commitment: affective commitment, continuance commitment and normative commitment significantly influenced employee turnover intention.